The Influence of Self-Efficacy on Entrepreneurship Intention Mediated by Sharia Entrepreneurship Behavior in the Context of Islamic Students' Education - Istikhayatin, Istikhayatin; Soelistya, Djoko (Journal La Edusci, 2025)
This study aims to determine the effect of self-efficacy and Sharia Entrepreneurship Education on entrepreneurial intentions in Surabaya Islamic students. This study uses a quantitative method with an associative explanatory approach. The data analysis technique used is in the form of multiple linear analysis with hypothesis taking using path analysis. The results of this study are in the form of a positive and significant relationship between self-efficacy and entrepreneurial intentions with a significance value of 0.000. Furthermore, the results obtained are that Sharia Entrepreneurship Education significantly influences student entrepreneurial intentions with a significance of 0.000. That is, the higher the self-efficacy that is owned and accompanied by qualified knowledge about entrepreneurship, the more it increases the intention of Surabaya Islamic students in entrepreneurship. Then Sharia Entrepreneurship Education was significantly successful in mediating between self-efficacy and student entrepreneurial intentions with the results of the Sodel test with a tcount of 7.190 (t count > t table, namely 1.976). This means that H0 is rejected and Ha is accepted or it can be concluded that self-efficacy has a positive and significant influence on Entrepreneurial Intentions through Sharia Entrepreneurship Education.